1982
DOI: 10.1002/jez.1402220111
|View full text |Cite
|
Sign up to set email alerts
|

Bovine serum albumin, sperm motility, and the “dilution effect”

Abstract: Epididymal spermatozoa from rabbit and ram were washed either once or twice using an efficient washing procedure and were then diluted in various media to a final concentration of approximately 1.4 x 10(7) cells/ml and incubated at 30 degrees C for up to 12 hours. Bovine serum albumin (BSA), either untreated or defatted, was found to be better than polyvinylpyrrolidone, ovalbumin, or alpha-lactalbumin, both at stimulating and maintaining motility levels and at reducing the tendency of the washed spermatozoa to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
1
1

Year Published

1985
1985
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 23 publications
1
61
1
1
Order By: Relevance
“…Both media also contained 1 mg poly(vinyl) alcohol/ml and 1 mg polyvinylpyrrolidone/ml, and had an osmolality of 305 mOsm/kg. Ejaculated ram spermatozoa were separated from seminal plasma by dilution and washing through sucrose medium (400×gm~ for 5 min, and 1000×gm~x for 10 min), as described [26].…”
Section: Preparation Labelling and Treatment Of Spermatozoamentioning
confidence: 99%
“…Both media also contained 1 mg poly(vinyl) alcohol/ml and 1 mg polyvinylpyrrolidone/ml, and had an osmolality of 305 mOsm/kg. Ejaculated ram spermatozoa were separated from seminal plasma by dilution and washing through sucrose medium (400×gm~ for 5 min, and 1000×gm~x for 10 min), as described [26].…”
Section: Preparation Labelling and Treatment Of Spermatozoamentioning
confidence: 99%
“…Although the specific mechanisms whereby albumin exerts its effects are not clearly defined, Lui, Cornett & Meizel (1977) have reported that albumin is required for induction of the acrosome reaction in hamster spermatozoa and that the fatty acid content of albumin can either enhance or inhibit acrosome loss . Albumin is also very effective in maintaining sperm motility during extended incubation in vitro (see for example Lui et ai, 1977;Suter, Chow & Martin, 1979;Harrison, Dott& Foster, 1982). Since motility is required for fertilization of eggs, at least those with intact investments, this may represent another facet of the albumin requirement.…”
Section: Introductionmentioning
confidence: 99%
“…AeG and SFM possessed greater ability in preserving spermatozoa motility, which reached the 60% threshold at the end of the trial. These two diluents contain BSA, which has been shown to have a potent effect on the stimulation (Harrison et al, 1982;Waberski et al, 1989) and preservation of motility.For viability, we experienced the best results with AeG and SFM, which were able to preserve membrane integrity more efficiently and for more days as compared with the other extenders. AeG and SFM can provide better conditions with a more controlled pH and osmotic pressure.…”
mentioning
confidence: 99%
“…AeG and SFM possessed greater ability in preserving spermatozoa motility, which reached the 60% threshold at the end of the trial. These two diluents contain BSA, which has been shown to have a potent effect on the stimulation (Harrison et al, 1982;Waberski et al, 1989) and preservation of motility.…”
mentioning
confidence: 99%